Elimination of methane in exhaust gas from biogas upgrading process by immobilized methane-oxidizing bacteria. (May 2017) - Wu, Ya-Min; Yang, Jing; Fan, Xiao-Lei; Fu, Shan-Fei; Sun, Meng-Ting; Guo, Rong-Bo
Highlights: Porous active carbon was successfully made from biogas digestate. Active carbon was used as immobilized material for MOB. Biofilter with immobilized MOB showed higher methane-oxidizing efficiency. Low concentration of methane can be efficiently disposed by immobilized MOB. Abstract: Biogas upgrading is essential for the comprehensive utilization of biogas as substitute of natural gas. However, the methane in the biogas can be fully recovered during the upgrading process of biogas, and the exhaust gas produced during biogas upgrading may contain a very low concentration of methane. If the exhaust gas with low concentration methane releases to atmosphere, it will be harmful to environment. In addition, the utilization of large amounts of digestate produced from biogas plant is another important issue for the development of biogas industry. In this study, solid digestate was used to produce active carbon, which was subsequently used as immobilized material for methane-oxidizing bacteria (MOB) in biofilter. Biofilter with MOB immobilized on active carbon was used to eliminate the methane in exhaust gas from biogas upgrading process. Results showed porous active carbon was successfully made from solid digestate. The final methane elimination capacity of immobilized MOB reached about 13 mol h −1 m −3, which was more 4 times higher than that of MOB without immobilization.